Product quality, network effects, and efficiency of network markets - Zhao, Dan; Song, Yan (Frontiers in Psychology, 2022)
The objective of our study is to capture the roles of product quality and network effects in the success and efficiency of network markets under strategic settings that defined in terms of market share as a strategic factor and profit as a financial indicator. The research paper shows that the efficiency of network markets depends heavily on the phase adjustment of competition models and the balance of network effects and product quality among enterprises. the network market is always efficient in price competition, but not true in quantity competition when the network effect difference is sufficiently large or/and the quality difference is relatively small, then network effects may play a perverse role in market efficiency. The main findings reveal that network effects do not always enhance the role of quality in market efficiency and market growth. The research outcomes point to high-quality enterprises’ attitude towards compatibility with enterprises with large network effects. This research paper also offers insights on government intervention to correct the distorted impacts of sufficiently large network effects on the efficiency of network markets.